Größenwachstum und Knochengesundheit bei Erkrankungen der Wachstumsfuge und des Knochens: Möglichkeiten und Grenzen einer GH-Therapie - Wölfle, Joachim; Bettendorf, M.; Bechtold-Dalla Pozza, S.; Binder, G.; Grasemann, C.; Reinehr, T.; Semler, O.; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2020)
Background: Genetic, paracrine and endocrine factors influence longitudinal growth in the area of the epiphyseal plates and bone mineralization. Objective: The aim was to review the spontaneous longitudinal growth and bone health in patients with rare bone diseases. Can growth hormone (GH) treatment improve growth and bone health in these diseases? Material and methods: Findings of an expert workshop including literature search on bone health in bone disorders associated with stunted growth and the treatment options. Results: Most patients with osteogenesis imperfecta are of short stature. Additional administration of GH has no influence on adult height and is currently not used. Pseudohypoparathyroidism (PHP) patients with insufficient longitudinal growth and confirmed GH deficiency can be treated with GH and can benefit from the treatment. Children with X‑linked hereditary hypophosphatemic rickets show progressive disproportionate short stature under the current treatment with phosphate and calcitriol. Randomized GH treatment studies resulted in a temporary improvement in body height but not in a significant improvement of adult height. The use of GH is approved for treatment of SHOX-deficient children and is comparably effective as in girls with Turner’s syndrome (TS). Observational studies also suggest that GH treatment can lower the risk of bone fractures, known to be increased in TS. Inflammation, reduced physical activity and malnutrition can result in impaired growth with loss of muscle and bone mass in patients with juvenile idiopathic arthritis (JIA). Studies could demonstrate a positive impact of GH on longitudinal growth, density and geometry of bones and on bone metabolism as well as on muscular mass; however, GH treatment is not approved for patients with JIA. Conclusion: Regarding the various bone diseases mentioned above, all growth disorders have to be considered individually. Apart from longitudinal growth GH can have a positive impact on metabolism, bone mineral content and bone density depending on the indications. The only approved indications for GH treatment are GH deficiency in PHP and children born small for gestational age (SGA) and TS/SHOX deficiency. Apart from increased growth, improvements in bone health in children and adolescents should be discussed as an outcome measure for GH treatment.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Bone; Bone health; Growth; Growth hormone (GH); Growth plate